Wheat stripe rust disease: Quantitative profiling of YR10 gene - (:unkn) unknown (Parlar Scientific Publications, 2017)
Yellow rust the destructive fungal disease of wheat (Triticum aestivum L.), caused by Puccinia striiformis f. sp. tritici (PST) results in high yield losses especially in the areas of epidemics frequently occurred in wheat all over the world. In this study, expression pattern of a yellow rust disease resistance gene (Yr10) in yellow rust resistant winter type bread wheat (Triticum aestivum L.) gene pool were investigated. Yr10 gene real-time gene expression profile of Yr10 gene was performed in Turkmen, Gerek79 and Avocet Yr10 as a positive control at 7 different time points (0 hour - MOCK, 15 minutes, 12 hours, 24 hours, 48 hours, 72 hours, 96 hours) after inoculation. It was observed that the most dramatic downregulation time point was 24 hpi for Yr10 gene expression in all genotypes. After 24 hpi, expression pattern was followed by upregulation in all genotypes at 48 phi. Avocet Yr10 genotype had downregulation pattern at 72 hpi while Turkmen and Gerek79 continue having the upregulation pattern till 96 hpi. In conclusion, expression of Yr10 gene was fluctuated depends on short-range time scale among 3 genotypes. In the future, the increased time points for expression profiling are required for more effective evaluation of stripe rust resistance response in wheat. For better evaluations of the plant response to yellow rust attack can be done via connecting interactions among cellular responses at different molecular levels for all special crops. Our study is a good model to move forward the studies at RNA level for yellow rust resistance. © by PSP.
Keywords: Bread wheat; Gene expression; Inoculation; Real-time PCR; Yellow rust; YR10 gene